Analisis Pendidikan Moral Dalam Perspektif Filsafat - Andi Muh. Fadhal Hiqh. T. Pangera; Muhammad Syukur (Journal on Education, 2024)
This research aims to find out; 1) The philosophical perspective in moral education, 2) The role of philosophy in the formation of student morals, and 3) The implementation of moral education. This type of research is a literature study that uses a content analysis approach. Data collection in this study comes from SINTA journal articles and Google Scholar. The results showed that; 1) In perspective, philosophy is fundamental in moral education because it offers a conceptual foundation for understanding the values, norms, and principles that guide human behavior as in the perspective of the philosophy of progressivism. Utilitarianism and deontology have their respective perspectives. 2) The role of philosophy in the context of education is to improve the morals and behavior of students. Education is held to hone the ability to think and the intelligence of reason. philosophy plays a key role in shaping students' morality by providing them with critical thinking skills, broadening their understanding of universal values, and fostering a sense of social responsibility, and 3) Implementation of moral education is applied in various ways, apart from in the classroom such as conducting programs, activities, or extracurricular activities. the application of moral education in schools is carried out with a child-centered approach. Children are encouraged to gain direct experience in understanding and applying moral values.